Strategi Pemasaran Online dan Pencegahan Penipuan Eradigitalisai - Dyas Yudi Priyanggodo; Endaria Endaria; Dedy Alamsyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Online marketing, also known as digital marketing, involves promoting products or services through digital mediums such as the Internet, mobile devices, and social platforms. It involves using different strategies to achieve business goals, such as increasing brand awareness, generating leads or customers, increasing sales, and building relationships. customer system. Phishing is a technique in which scammers attempt to trick victims into providing personal information such as passwords, credit card numbers, or other financial information by pretending to be a trustworthy organization through fake email or fake website.